Varietal impact on women's labour, workload and related drudgery in processing root, tuber and banana crops. Focus on cassava in sub-Saharan Africa - Bouniol, A.; Ceballos, H.; Bello, A. A.; Teeken, B.; Olaosebikan, O.; Owoade, D.; Agbona, A .; Fotso Kuate, A.; Madu, Tessy; Okoye, B.; Ofoeze, M.; Nwafor, S.; et al. (Wiley, 2024)
Roots, tubers and cooking bananas are bulky and highly perishable. In Africa, except for yams, their consumption is mainly after transport, peeling and cooking in the form of boiled pieces or dough, a few days after harvest. To stabilize, better preserve the products and, in the case of cassava, release toxic cyanogenic glucosides, a range of intermediate products have been developed, mainly for cassava, related to fermentation and drying after numerous processing operations. This review highlights, for the first time, the impact of genotypes on labour requirements, productivity, and the associated drudgery in processing operations primarily carried out by women processors. Peeling, soaking/grinding/fermentation, dewatering, sieving, and toasting steps were evaluated on a wide range of new hybrids and traditional landraces. The review highlights case studies of gari production from cassava. Results show that, depending on the genotypes used, women's required labour can be more than doubled and even the sum of the weights transported along the process can be up to four times higher for the same quantity of end product. Productivity and loads carried between each processing operation are highly influenced by root shape, ease of peeling, dry matter content and/or fiber content. Productivity and the often related experienced drudgery are key factors to be considered for a better acceptance of new genotypes by actors in the value-addition chain, leading to enhanced adoption, and ultimately to improved livelihoods for women processors.